1999
DOI: 10.1524/zpch.1999.212.part_1.099
|View full text |Cite
|
Sign up to set email alerts
|

Structural Control of Semiconductor Surfaces on Atomic and Nanometer Scales for Efficient Solar Energy Conversion

Abstract: Photoelectrochemistry I Solar cells I Small metal particle I Porous silicon I Surface termination bondStructural control of semiconductor surfaces on an atomic scale and that on a nanometer scale are both important for efficient solar energy conversion. The former is important for achieving low surface carrier recombination, high catalytic activity for interfacial reactions, formation of high energy barriers, etc. The latter is important for simultaneous achievement of all these requirements at one surface, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 13 publications
0
14
1
Order By: Relevance
“…Surface dipoles arising from polar surface bonds cause a substantial surface potential difference at silicon/electrolyte, [18][19][20][21] silicon/silicon-oxide, and silicon/metal interfaces. 46,47 First principle calculations 46 for the silicon/silicon-oxide interface revealed that a complete replacement of Si-H termination by Si-OH increases the interfacial potential by approximately 1 V. Therefore, polarized surface bonds are also expected to play an important role in the present system.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Surface dipoles arising from polar surface bonds cause a substantial surface potential difference at silicon/electrolyte, [18][19][20][21] silicon/silicon-oxide, and silicon/metal interfaces. 46,47 First principle calculations 46 for the silicon/silicon-oxide interface revealed that a complete replacement of Si-H termination by Si-OH increases the interfacial potential by approximately 1 V. Therefore, polarized surface bonds are also expected to play an important role in the present system.…”
Section: Discussionmentioning
confidence: 99%
“…The flat band potential (E FB ) of silicon in contact with an electrolyte depends on the surface groups present. [18][19][20][21] This has been demonstrated when Si-OH groups are replaced by Sihalogen groups [18][19][20] and for the chemical formation of Si-OCH 3 surface groups. 21 These shifts have been attributed to surface potential changes due to polar surface bonds.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We reported previously , that the flat-band potentials ( U fb ) of HF-etched n-Si(100) and -(111) in concentrated hydrogen halide (HX) solutions shifted largely toward the negative in the order HF, HCl, HBr, and HI, and explained the shifts to be due to changes in surface potential by formation of Si−X bonds through substitution reaction at surface Si−OH bonds. We reported later that Si−H bonds on H−Si(111) were also changed to Si−X in the concentrated HX solutions if an oxidant such as dissolved air, Br 2 , and I 2 was contained, though the Si−H bonds were stable in the absence of the oxidant.…”
Section: Introductionmentioning
confidence: 99%